Strategi Lembaga Amil Zakat dalam Meningkatkan Akses Sanitasi dan Air Bersih (Studi Kasus LAZ Harfa Serang) - Amalia, Rika Yulita; Nurwahidin, Nurwahidin; Huda, Nurul (ZISWAF, 2020)
Sustainable Development Goals (SDGs), which is a world development agenda, raised one of the issues that became the objectives of its achievement targets, namely related to sanitation and clean water. Various adverse effects can be caused by inadequate sanitation and clean water conditions, including diarrhea, stunting, and even death. Therefore, several parties are trying to overcome this problem, bearing in mind the condition of sanitation and clean water in Indonesia still needs more attention. One of the parties concerned about the sanitation and clean water conditions is the Amil Zakat Harapan Duafa Institute (LAZ Harfa) Serang, Banten. LAZ Harfa has succeeded in changing the behavior of around 50,000 people who previously had open defecation habits to become accustomed to defecating in their place. This paper aims to find out the strategies carried out by LAZ Harfa so that it can succeed in carrying out the program. The method used in this study is a semi-structured interview with related parties. The results showed that the main strategy of LAZ Harfa in carrying out the sanitation and clean water program was by conducting education, optimizing the role of facilitator facilitators, cooperating, engaging the community directly, and cooperating with various partners.